A Chromosome level assembly of pomegranate (Punica granatum L.) variety grown in arid environment - Himanshu V. Patankar; Luis F. Rivera; Fatima Omari Alzahrani; Rod A. Wing; Ikram Blilou (Scientific Data)
Abstract The pomegranate (Punica granatum L.) is an ancient fruit-bearing tree known for its nutritional and antioxidant properties. They originated from the Middle East in regions having large farms including mountainous regions of Al-Baha in Saudi Arabia. Pomegranates can tolerate arid climates and are considered among the fruits that will play a major role in food security. However, the genomics resources of pomegranate growing in arid regions are scarce. Here, we present a high-quality chromosome-level reference genome using PacBio HiFi long reads. The final assembly was 384.65 Mb with N50 contig size of 43.11 Mb, with 353.42 Mb being anchored on the eight pseudo chromosomes. Annotation revealed that 48.79% of the genome comprises repetitive elements and contains 21,620 protein-coding genes. The new reference genome will contribute to identifying stress resistance traits in pomegranates thriving in arid environments as well as new dietary antioxidants and antimicrobial peptides with pharmaceutical and therapeutic applications.